Fashion design : d'artiste : digital artists master class. - Zambonin, Alessia, ....-; Stegg, Annie, ....-; Van Baarle, Lois, ....- (Adelaide : Ballistic, 2012)
Fashion Design features talented fashion artists Alessia Zambonin, Annie Stegg, and Lois van Baarle, who show you the painting and design techniques to create compelling costume designs for characters. Each page is jammed full of techniques and approaches that will take your design and illustration skills to the next level. An invited artist gallery showcases the artists whose work inspires and excites the featured artists, and they offer creative commentaries on what makes the invited work great. This, the twelfth book in the d'artiste series, sets the standard for inspiration with a wide selection of fashion styles and influences